'Opt-out' referrals after identifying pregnant smokers using exhaled air carbon monoxide: impact on engagement with smoking cessation support. Issue 3 (25th May 2016) - Campbell, Katarzyna A; Cooper, Sue; Fahy, Samantha J; Bowker, Katharine; Leonardi-Bee, Jo; McEwen, Andy; Whitemore, Rachel; Coleman, Tim
Abstract : Background: In the UK, free smoking cessation support is available to pregnant women; only a minority accesses this. 'Opt-out' referrals to stop smoking services (SSS) are recommended by UK guidelines. These involve identifying pregnant smokers using exhaled carbon monoxide (CO) and referring them for support unless they object. Methods: To assess the impact of 'opt-out' referrals for pregnant smokers on SSS uptake and effectiveness, we conducted a 'before–after' service development evaluation. In the 6-month 'before' period, there was a routine 'opt-in' referral system for self-reported smokers at antenatal 'booking' appointments. In the 6-month 'after' period, additional 'opt-out' referrals were introduced at the 12-week ultrasound appointments; women with CO≥4 ppm were referred to, and outcome data were collected from, local SSS. Results: Approximately 2300 women attended antenatal care in each period. Before the implementation, 536 (23.4%) women reported smoking at 'booking' and 290 (12.7%) were referred to SSS. After the implementation, 524 (22.9%) women reported smoking at 'booking', an additional 156 smokers (6.8%) were identified via the 'opt-out' referrals and, in total, 421 (18.4%) were referred to SSS. Over twice as many women set a quit date with the SSS after 'opt-out' referrals were implemented (121 (5.3%, 95% CI 4.4% to 6.3%) compared to 57 (2.5%, 95% CI 1.9% to 3.2%) before implementation) and reported being abstinent 4 weeks later (93 (4.1%, 95% CI 3.3% to 4.9%) compared to 46 (2.0%, 1.5% to 2.7%) before implementation). Conclusions: In a hospital with an 'opt-in' referral system, adding CO screening with 'opt-out' referrals as women attended ultrasound examinations doubled the numbers of pregnant smokers setting quit dates and reporting smoking cessation.